1991
DOI: 10.1001/archsurg.1991.01410360031006
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Implications of Microscopic Satellites in Patients With Clinical Stage I Melanoma

Abstract: Controversy exists as to whether microscopic satellites influence prognosis or patterns of progressive disease in patients with clinical stage I melanoma. Fifty patients with clinical stage I melanoma and microscopic satellites were prospectively studied from 1972 to 1984. To allow for complete histopathology assessment, 30 patients with microscopic satellites who were prospectively seen from 1972 to 1979 were matched to a cohort of 77 patients with vertical growth-phase melanoma without microscopic satellites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
2
4

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 23 publications
1
53
2
4
Order By: Relevance
“…The presence of clinical or microscopic satellite metastases around a primary melanoma as well as in-transit metastases between the primary melanoma and the regional lymph nodes represent intralymphatic metastases and portend a poor prognosis. 4,[40][41][42][43] The available data show no substantial difference in survival outcome for these two anatomically defined entities. 4 Therefore, they are both assigned to a separate N2c classification in the absence of synchronous nodal metastases because both have a prognosis equivalent to multiple nodal metastases (Tables 2 and 3).…”
Section: Intralymphatic Metastasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of clinical or microscopic satellite metastases around a primary melanoma as well as in-transit metastases between the primary melanoma and the regional lymph nodes represent intralymphatic metastases and portend a poor prognosis. 4,[40][41][42][43] The available data show no substantial difference in survival outcome for these two anatomically defined entities. 4 Therefore, they are both assigned to a separate N2c classification in the absence of synchronous nodal metastases because both have a prognosis equivalent to multiple nodal metastases (Tables 2 and 3).…”
Section: Intralymphatic Metastasesmentioning
confidence: 99%
“…The presence of clinical or microscopic satellite metastases around a primary melanoma as well as in-transit metastases between the primary melanoma and the regional lymph nodes represent intralymphatic metastases and portend a poor prognosis. 4,[40][41][42][43] The available data show no substantial difference in survival outcome for these two anatomically defined entities.4 Therefore, they are both assigned to a separate N2c classification in the absence of synchronous nodal metastases because both have a prognosis equivalent to multiple nodal metastases (Tables 2 and 3). Furthermore, the available data demonstrate that patients with a combination of satellites and in-transit metastases plus nodal metastases have a worse outcome than patients who experience either event alone, so these patients were assigned to a N3 classification regardless of the number of synchronous metastatic nodes (Tables 2 and 3).…”
mentioning
confidence: 99%
“…10,53,[86][87][88][89] Clark et al 10 found a reduction of actuarial 8-year survival from 75 to 40% when satellites were identified. It has been suggested that this is a difficult criterion to assess, as tumor tongues radiating from the main vertical growth phase nodule may mimic satellites due to artifacts of sectioning.…”
Section: Microscopic Satellitesmentioning
confidence: 99%
“…Subsequent survival analyses have revealed decreased survival and increased probabilityofregionalrelapseamongpatients with evidence of microsatellites in their primary tumor. 2,3 Recently, the latest version of the American Joint Committee on Cancer (AJCC) staging classification for melanoma 4 has up-staged microsatellites to the N classification of the TNM system. Specifically, patients with microsatellites are assigned to the pathologic N2c and clinical IIIB staging categories, prognostically placing them alongside patients with intransit and clinical satellite metastases (macrosatellites).…”
Section: Firstmentioning
confidence: 99%